Polycystic ovarian syndrome: affecting quality of life and awaiting cure - Mathur, Shikha (International Journal of Research in Medical Sciences, 2025)
Background: The increasing number of polycystic ovarian syndrome (PCOS) patients in gynaecology outdoor especially younger adults, with long term health implications prompts us to study the condition. The syndrome not only has a vast impact on physical health but also affects psychosocial aspects of life. The study aimed to analyse the characteristics and presenting complaints in subjects with PCOS. Methods: It was an observational study conducted at a secondary care centre over a period of one year. Chi square goodness of fit test was used to analyse the results. Results: The study showed an increased incidence in younger adults with menstrual irregularity as the most common complaint and an increased body mass index (BMI) amongst most patients. Inability to conceive without treatment was also very important presenting feature. Conclusions: We should increase our efforts to find a preventive strategy and if possible, a cure to this syndrome.